PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL DAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERATING - Koeshardjono, R. Hery; Priantono, Seger; Amani, Tatik (Universitas Muhammadiyah Jember, 2019)
The purpose of this study is to partially prove the influence of CSR, Company Size, Leverage, Profitability to Company Value with managerial ownership and independent commissioners as a Moderating variable. While the specific targets to be achieved are; to prove that managerial ownership and independent commissioner variables greatly influence or weaken the relationship of CSR Variables, Company Size, Leverage, Profitability to Company Value. This research is categorized into descriptive research using quantitative methods that are causality. Whereas the method that will be used in achieving the goal by using some descriptive statistical analysis techniques with the classic assumption test tool, besides that hypothesis testing consists of; coefficient determinant test (R2), partial significance test (t test) and calculation of Moderated Regression Analysis (MRA) with SPSS.The population used in this study is a coal mining company that is on the Indonesia Stock Exchange (IDX) during the 2014-2018 period with sampling according to predetermined criteria.The results of the research partially that CSR, Company Size, and Profitability do not significantly influence the Company Value, but Leverage significantly influence the Company Value. Likewise, the Moderating Variable analysis with the MRA interaction test method shows that partially Managerial Ownership and Independent Commissioner variables can strengthen the relationship between CSR, Company Size, Leverage and Profitability to Company Value.